Relevance of child stunting as an outcome of interest in programs targeting undernutrition - CGIAR Research Program on Agriculture for Nutrition and Health (2019)
Since it was published, the study has been extensively cited. Donors - the Department for International Development, the United States Agency for International Development, and the World Bank - reported that the research has had an impact on their decisions around which nutrition outcomes to focus when funding/designing programs.